Determination of the best time of harvest in different commercial Iranian pistachio nuts - Panahi B.; Mirdamadiha F.; Talaie A. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
One of the most important factors affecting pistachio nuts quality is harvest time. Early hull splitting in pistachio fruits is one of the most considerable problems in orchards. These split fruits cause contamination with the Aspergillus sp. fungus. The kind of cultivar and harvest time are important factors determining early hull splitting and yield quality. This study was carried out on four commercial Iranian pistachio cultivars. A factorial design was laid out at the Rafsanjan area. Percentage of hulling, blank and immature fruits, early hull splitting, splitting-non-splitting, hull cracking, number of nuts per 100 g dried nuts, kernel-nut ratio, kernel humidity, sucrose, oil and, finally, aflatoxin B1 and B2 content were measured. Almost all the quality differences between cultivars were associated with harvest time with significant differences. 'Ahmad-Aghaei' was of substantially better quality than the other cultivars. The middle to end of September was determined as the best time to harvest.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)